Comparison of conventional Papanicolaou smear and liquid‑based cytology: a study of cervical cancer screening at a tertiary care center in Bengaluru - Krishna, Chaitra; Chandraiah, Savitha; Krishna, Chandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cervical cancer is the fourth commonest cancer affecting women worldwide and the second most common cancer in women aged 15-44 years. The Papanicolaou (Pap) smear has been the cornerstone of screening for cervical neoplasm for the last 50 years. Liquid-based cytology (LBC) was introduced in mid-1990s as an alternative technique to process cervical samples has many benefits over Pap. A new second generation technique, Liquiprep was introduced after a decade has the advantage of a much lower cost. However, the information available on second generation liquid based cytology is limited. The objective was to look for the efficacy of LBC and to compare it to that of conventional cytology. Methods: This hospital based comparative study was undertaken 100 women who attended gynaecology OPD during 2017 at a tertiary care hospital in Bengaluru. Two cervical smears were simultaneously prepared from each subject, one for Pap smear and another for LBC followed by colposcopy and biopsy. Results: Among the study subjects, 89% of Pap smear analysis and 100% of smears in LBC showed satisfactory smear. Cytological abnormality was detected in 11% and 21% in pap and LBC, respectively. The present study showed higher sensitivity and specificity of 100% and 75% by LBC when compared to Pap smear (55% and 100% respectively). Conclusions: The present study showed that liquid based cytology is better in detecting cervical lesions when compared to conventional smear.